THE IMPACT OF FINANCIAL TECHNOLOGY TOWARDS FINANCIAL INCLUSION DEVELOPMENT IN SMES IN WEST JAVA, INDONESIA - Hermanto Joesoef (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this study is to analyze the effect of fin-tech (risk and investment management, market provisioning, and cashless society) on financial inclusion (financial knowledge, financial behavior, and financial attitudes) in SMEs in West Java. This research is a quantitative research. The data of this research is based on the SME industry in West Java. This research uses descriptive analysis and classical assumption test. The research shows that simultaneously and partially the fin-tech variable (risk and investment management and market provisioning) has no effect on financial inclusion (financial knowledge, financial behavior, and financial attitudes), whereas simultaneously and partially, the fin-tech (cashless society) variable has an effect on financial inclusion (financial knowledge, financial behavior, and financial attitudes).